Economic challenges on micro enterprise contractors in surviving Covid-19 pandemic's effects / Norsyakilah Romeli ... [et al.] - Romeli, Norsyakilah; Husni, Nur Izzati Nazifa; Muhamad Halil, Faridah; Abd Ghapar, Muhammad Aizat Afiq; Dhelbi, Jacqueline Wena (Universiti Teknologi MARA, 2022)
The outbreak of Covid-19 pandemic has disrupted the global economy, leading Malaysia's economy to suffer. Since the start of lockdown, numerous construction companies have suffered in maintaining their financial business especially for micro business since they are financially fragile in contrast to large business. Hence, this study aims to investigate the economic challenges effected by Covid-19 towards micro enterprise contractor's survival. This study adopted mix method approach which is quantitative data and qualitative data. Both collection of data were handled via online medium to avoid the spread of Covid-19 virus. Financial issues factor, cost implication, and financial mitigation are the major variable variables that observed in the survey. This is based on a financial issue factors, which includes implementation of movement control order, standard operating procedure, material construction price increases, payment issues, and client-related factors. As the results the implementation of movement control order, increase price of construction material, new standard operation procedure, payment issue and client related factor has effected the most on the financial issues sides meanwhile on cost implication sides, the cost overrun has effectedmicro entreprise during pandemic. Results on financial mitigation were obtained to mitigate the impact of Covid-19, with the results indicating that invoking force majeure, government financial aid, joint venture plans, company termination, and risk sharing can help micro enterprises cope with the difficulty. Therefore, this helps micro enterprise to survive the economic impact and understand the challenges of the pandemic by adopting an effective strategy that will help improve the financial company management.